Implementasi Kapita Selekta Matematika dalam Mengembangkan Higher Order Thinking Skills (HOTS) Mahasiswa Calon Guru: Sebuah Kajian Literatur Sistematis (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to analyze the role of the Selected Topics in Mathematics course in developing Higher Order Thinking Skills (HOTS) among prospective mathematics teachers through a systematic literature review. The review covered 21 articles published between 2020 and 2025, sourced from nationally accredited Sinta-indexed journals and reputable international journals. The research employed the Systematic Literature Review (SLR) method, following the stages of data reduction, data display, and verification and interpretation based on the model by Miles, Huberman, and Saldaña (2014). The analysis revealed that the implementation of problem-based learning and inquiry-based learning strategies is effective in enhancing students’ abilities in analysis, evaluation, and creation. The use of authentic assessments such as projects and reflective rubrics proved to be more comprehensive in measuring higher-order thinking processes compared to conventional tests. Key challenges identified include limited lecturer training, lack of contextual teaching materials, and insufficient technological support. This study confirms the strategic potential of the Selected Topics in Mathematics course in fostering HOTS among prospective teachers and offers recommendations for strengthening the curriculum and developing HOTS-based assessments in higher education.